EDUKASI DESAIN ERGONOMIS FASILITAS BELAJAR BERDASARKAN DATA ANTROPOMETRI DI PAUD KELURAHAN AIE PACAH - Melya Susanti,; Ira Suryanis,; Rinita Amelia,; Raham Triyana, (Nusantara Hasana Journal, 2023)
Early childhood, the golden age of growth and development for children, is a very critical period in the stage of human development. Since 2003, the government has issued Law No. 20 of 2003 concerning the national education system, including the PAUD education system (early childhood education). According to the Ministry of Education and Culture, in the 2020–2021 school year, 6,346,193 early childhood education students in Indonesia were members of private and public educational institutions. According to early childhood education statistics, more classrooms are lightly damaged than good. The learning process in early childhood education institutions takes place actively and involves children who are at the most active and energetic stage, so they need ergonomic learning facilities whose size is determined by the child's body size and which are comfortable and safe. The ergonomic design of this learning facility also aims to maintain bone health and early childhood posture because it is still vulnerable and easy to change. After all, it is still in its infancy. Evaluation of school benches, measurement of children's anthropometric data, and education on the importance of using ergonomic school equipment have been carried out in one of the PAUD/TK locations in the Koto Tangah sub-district. The results obtained by the school bench used are quite ergonomic when compared to the anthropometric size of students at the school.